Kiai Communication's Contribution to Enhancing Organisational Effectiveness - Nur Khamid (Al-Qalam Institute, 2024)
This study aims to examine the role of Kiai communication in improving organizational performance in Islamic Boarding Schools. This study focuses on the communication strategies used by Kiai, especially in bridging internal and external communication channels to strengthen the identity of the Islamic boarding school. A qualitative case study approach was used to collect data through interviews, observations, and document analysis with data analysis, according to Miles and Huberman. The findings of the study revealed that the charismatic and empathetic communication style of Kiai fosters loyalty among students, administrators, and the wider community, thereby improving organizational performance. This study is expected to contribute to understanding how effective leadership communication can create a cohesive and high-performance educational environment and provide insights for other Islamic boarding schools that want to strengthen their organizational dynamics through communication.